The value proposition of integrative diagnostics for (early) detection of cancer: on behalf of the EFLM interdisciplinary Task and Finish Group “CNAPS/CTC for early detection of cancer” : EFLM paper - Froelich, Matthias F.; Capoluongo, Ettore; Kovacs, Zsolt; Patton, Simon J.; Lianidou, Evi S.; Haselmann, Verena (Clinical chemistry and laboratory medicine, 2022)
Disruptive imaging and laboratory technologies can improve clinical decision processes and outcomes in oncology. However, certain obstacles must be overcome before these technologies can be fully implemented as part of the standard for care. An integrative diagnostic approach represents a unique opportunity to unleash the full diagnostic potential and paves the way towards personalized cancer diagnostics. To meet this demand, an interdisciplinary Task Force of the EFLM was initiated as a consequence of an EFLM/ESR during the CELME 2019 meeting in order to evaluate the clinical value of CNAPS/CTC (circulating nucleic acids in plasma and serum/circulating tumor cells) in early detection of cancer. Here, an overview of current disruptive techniques, their clinical implications and potential value of an integrative diagnostic approach is provided. Furthermore, requirements such as the establishment of diagnostic tumor boards, development of adequate software solutions and a change of mindset towards a new generation of diagnosticians providing actionable health information are presented. This development has the potential to elevate the position and clinical recognition of diagnosticians.
Gesehen am 20.02.2024